## Results (displaying matches 1-50 of 30579) Next

Label Class Equation Sato-Tate $$\overline{\Q}$$-simple $$\GL_2$$ Rank*
587.a.587.1 587.a $$y^2 + (x^3 + x + 1)y = -x^2 - x$$ $\mathrm{USp}(4)$ 1
713.a.713.1 713.a $$y^2 + (x^3 + x + 1)y = -x^5 - x$$ $\mathrm{USp}(4)$ 1
743.a.743.1 743.a $$y^2 + (x^3 + x + 1)y = -x^4 + x^2$$ $\mathrm{USp}(4)$ 1
847.a.847.1 847.a $$y^2 + (x^3 + x^2 + x + 1)y = x^4 + x^3 + x^2$$ $G_{3,3}$ 1
893.a.893.1 893.a $$y^2 + (x^3 + x + 1)y = -x^4 - x^2$$ $\mathrm{USp}(4)$ 1
932.a.3728.1 932.a $$y^2 + y = x^6 - 2x^5 + x^4 + x^2 - x$$ $\mathrm{USp}(4)$ 1
953.a.953.1 953.a $$y^2 + (x^3 + x + 1)y = x^3 + x^2$$ $\mathrm{USp}(4)$ 1
968.a.1936.1 968.a $$y^2 + y = x^6 - x^4$$ $G_{3,3}$ 1
968.a.234256.1 968.a $$y^2 + x^3y = 6x^4 + 47x^2 + 121$$ $G_{3,3}$ 1
971.a.971.1 971.a $$y^2 + y = x^5 - 2x^3 + x$$ $\mathrm{USp}(4)$ 1
997.b.997.1 997.b $$y^2 + y = x^5 - 2x^4 + 2x^3 - x^2$$ $\mathrm{USp}(4)$ 1
1051.a.1051.1 1051.a $$y^2 + y = x^5 - x^4 + x^2 - x$$ $\mathrm{USp}(4)$ 1
1062.a.6372.1 1062.a $$y^2 + (x^3 + 1)y = x^5 - x^4 + x^2 - x$$ $\mathrm{USp}(4)$ 1
1070.a.2140.1 1070.a $$y^2 + (x^3 + 1)y = x^3 - x$$ $\mathrm{USp}(4)$ 1
1077.a.1077.2 1077.a $$y^2 + (x^3 + 1)y = x^4 + x^3 + 2x^2 + x$$ $\mathrm{USp}(4)$ 1
1077.a.1077.1 1077.a $$y^2 + (x^3 + 1)y = 5x^5 + 34x^4 + 80x^3 - x^2 - 90x + 32$$ $\mathrm{USp}(4)$ 1
1083.a.1083.1 1083.a $$y^2 + (x^3 + x^2 + x + 1)y = -x^3$$ $G_{3,3}$ 1
1083.a.20577.1 1083.a $$y^2 + x^3y = x^5 - 5x^4 + 11x^3 - 13x^2 + 9x - 3$$ $G_{3,3}$ 1
1091.a.1091.1 1091.a $$y^2 + (x^2 + x + 1)y = x^5 - 2x^3 - x^2$$ $\mathrm{USp}(4)$ 1
1094.a.2188.1 1094.a $$y^2 + (x^3 + 1)y = x^4 - x^2$$ $\mathrm{USp}(4)$ 1
1127.a.1127.1 1127.a $$y^2 + (x^3 + x + 1)y = -x^4 + x^3 - x^2 - x$$ $\mathrm{USp}(4)$ 1
1145.a.1145.1 1145.a $$y^2 + (x^3 + 1)y = -3x^4 + 3x^3 - x$$ $\mathrm{USp}(4)$ 1
1145.a.143125.1 1145.a $$y^2 + (x^3 + x^2 + x)y = 2x^4 + 4x^3 + 9x^2 + 10x + 9$$ $\mathrm{USp}(4)$ 1
1198.a.2396.1 1198.a $$y^2 + (x^3 + 1)y = -x$$ $\mathrm{USp}(4)$ 1
1205.a.1205.1 1205.a $$y^2 + y = x^5 + 2x^4 - x^2$$ $\mathrm{USp}(4)$ 1
1207.a.1207.1 1207.a $$y^2 + (x^2 + x + 1)y = -x^5 - x^4$$ $\mathrm{USp}(4)$ 1
1253.b.1253.1 1253.b $$y^2 + (x^3 + x + 1)y = x^4 + x^2$$ $\mathrm{USp}(4)$ 1
1269.a.1269.1 1269.a $$y^2 + (x^3 + x^2 + x + 1)y = x^2 + x$$ $\mathrm{USp}(4)$ 1
1300.a.130000.1 1300.a $$y^2 + (x^3 + x)y = 2x^4 + 9x^2 + 13$$ $G_{3,3}$ 1
1312.a.2624.1 1312.a $$y^2 + (x + 1)y = x^6 + 2x^5 + 3x^4 + 2x^3 + x^2$$ $\mathrm{USp}(4)$ 1
1327.a.1327.1 1327.a $$y^2 + (x^2 + x + 1)y = x^5 + 2x^4 + x^3$$ $\mathrm{USp}(4)$ 1
1331.a.1331.1 1331.a $$y^2 + x^3y = -x^4 - x^3 + 2x^2 + 3x + 1$$ $N(G_{1,3})$ 1
1338.a.2676.1 1338.a $$y^2 + (x^3 + x^2 + x)y = x^4 + x^3 + 2x^2 + x + 1$$ $\mathrm{USp}(4)$ 1
1343.a.1343.1 1343.a $$y^2 + (x^3 + x + 1)y = x^5 - 2x^4 - x$$ $\mathrm{USp}(4)$ 1
1343.b.1343.1 1343.b $$y^2 + (x^3 + x + 1)y = -3x^4 + x^3 + 2x^2 + x$$ $\mathrm{USp}(4)$ 1
1369.a.1369.1 1369.a $$y^2 + (x^3 + x^2 + x + 1)y = -x^4 - x^3 - x^2$$ $G_{3,3}$ 1
1369.a.50653.1 1369.a $$y^2 + x^3y = 2x^5 - 5x^4 + 7x^3 - 6x^2 + 3x - 1$$ $G_{3,3}$ 1
1383.a.4149.1 1383.a $$y^2 + y = x^5 + x^4$$ $\mathrm{USp}(4)$ 1
1385.a.6925.1 1385.a $$y^2 + y = x^5 + 3x^4 + 3x^3 - x$$ $\mathrm{USp}(4)$ 1
1397.a.1397.1 1397.a $$y^2 + y = x^5 - x^3$$ $\mathrm{USp}(4)$ 1
1403.a.1403.1 1403.a $$y^2 + y = x^5 + x^4 - x^3 - x^2$$ $\mathrm{USp}(4)$ 1
1415.a.1415.1 1415.a $$y^2 + (x^2 + x + 1)y = x^5 - 3x^4 + x^3 - x$$ $\mathrm{USp}(4)$ 1
1445.a.122825.1 1445.a $$y^2 + (x^3 + x^2 + x)y = 3x^4 + 4x^3 + 18x^2 + 10x + 29$$ $\mathrm{USp}(4)$ 1
1468.a.2936.1 1468.a $$y^2 + (x^3 + x + 1)y = -x^5 - x^2$$ $\mathrm{USp}(4)$ 1
1490.a.1490.1 1490.a $$y^2 + (x^3 + 1)y = x^5 - 4x^3 - 2x^2 + 2x$$ $\mathrm{USp}(4)$ 1
1497.a.1497.1 1497.a $$y^2 + (x^3 + x + 1)y = -x^4 + x^3 - 2x^2 + x - 1$$ $\mathrm{USp}(4)$ 1
1497.b.13473.1 1497.b $$y^2 + (x^3 + x + 1)y = -2x^5 + 3x^4 - x^2$$ $\mathrm{USp}(4)$ 1
1499.a.1499.1 1499.a $$y^2 + (x^3 + 1)y = -x^5 + x^2 - x$$ $\mathrm{USp}(4)$ 1
1503.a.4509.1 1503.a $$y^2 + (x^3 + x + 1)y = x^5 - x^4 - 3x^3 + x$$ $\mathrm{USp}(4)$ 1
1519.a.1519.1 1519.a $$y^2 + (x^3 + x + 1)y = -2x^4 + 2x^2 - x - 1$$ $\mathrm{USp}(4)$ 1
Next